Achnanthidium neotropicum sp. nov., a new freshwater diatom from Lake Apastepeque in El Salvador (Central America) - Krahn, Kim J.; Wetzel, Carlos E.; Ector, Luc; Schwalb, Antje (Phytotaxa, 2018)
A new freshwater diatom recovered from modern and subfossil sediments of Lake Apastepeque in El Salvador, Achnanthidium neotropicum sp. nov., is described based on light and scanning electron microscopy observations. The species is characterized by valves with linear, sometimes centrally constricted (mainly in large cells), outlines, broadly rounded to subrostrate apices, and often rectangular fascia. Striae are composed of 3–4 rounded to slit-like areolae. It can be separated from similar species by valve outline, together with striae density, and number of areolae per stria. Based on the straight distal raphe endings this species can be assigned to the A. minutissimum complex. The new species is compared to morphologically resembling species from the genus Achnanthidium Kützing.